Gamifying Audio Description Training - Zhang, Xiaochun (Journal of Audiovisual Translation, 2021)
State-of-the-art training methods for audio description (AD) are essential in preparing future professionals to meet the demand for accessible media content. Gamification, the application of game elements in non-game contexts, has been gaining increasing scholarly attention in the field of teaching and learning over the past few years. It is considered an effective pedagogical approach and has been applied in diverse contexts but not yet in AD training. This paper first provides a brief review of current AD teaching practice before investigating the implementation of gamification strategies in the language industry and in translator and interpreter training. It then introduces a gamified in-class activity based on the framework of Werbach and Hunter (2012). The process of gamification, the design of the activity, and its reception by students are presented and discussed. As it seems to be the first attempt at applying gamification to the teaching of AD, there is plenty of space for improvement and further gamification. Reflection and suggestions on the activity design and gamification as a pedagogical approach are thus provided in the hope of exploring new methods in AD teaching as well as other topics in translator and interpreter training. Lay summary Audio description (AD) is a service that verbally describes relevant visual elements of artwork or media products, making them accessible to blind and partially sighted users. Up-to-date training methods for AD are important in preparing future professionals to meet the demand for accessible media content. Gamification refers to the use of game elements in non-game contexts, which is considered an effective pedagogical approach and has been applied in diverse contexts but not yet in AD training. This paper first provides a brief review of current AD teaching practice before investigating gamification strategies in the language industry and in translator and interpreter training. It then introduces a gamified in-class activity and discusses the process of gamification, the design of the activity, and its reception by students. As it seems to be the first attempt at applying gamification to the teaching of AD, there is plenty of space for improvement and further gamification. Reflection and suggestions on the activity design and gamification as a teaching method are thus provided to explore new approaches in AD teaching and other topics in translator and interpreter training.